2018
DOI: 10.1186/s12906-018-2383-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of senescent human diploid fibroblasts treated with gamma-tocotrienol

Abstract: BackgroundReplicative senescence of human diploid fibroblasts (HDFs) has been used as a model to study mechanisms of cellular aging. Gamma-tocotrienol (γT3) is one of the members of vitamin E family which has been shown to increase proliferation of senescent HDFs. However, the modulation of protein expressions by γT3 in senescent HDFs remains to be elucidated. Therefore, this study aimed to determine the differentially expressed proteins (DEPs) in young and senescent HDFs; and in vehicle- and γT3-treated senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…1). A recent report showed that RPSA proteins were one of several differentially expressed proteins in senescent human diploid fibroblasts treated with gamma-tocotrienol (member of the Vitamin E family shown to increase proliferation of senescent fibroblasts) [56] , thus supporting the identification of prominent ribosomal protein subunit nodes in our network analysis.…”
Section: Discussionsupporting
confidence: 84%
“…1). A recent report showed that RPSA proteins were one of several differentially expressed proteins in senescent human diploid fibroblasts treated with gamma-tocotrienol (member of the Vitamin E family shown to increase proliferation of senescent fibroblasts) [56] , thus supporting the identification of prominent ribosomal protein subunit nodes in our network analysis.…”
Section: Discussionsupporting
confidence: 84%
“…GT3 can selectively inhibit the PI3K/Akt pathway, Ras/Raf/Erk signal transduction, HMG-CoA reductase and transcription factor NF-κB, and participate in the regulation of various physiological activities of the body ( Ahsan et al, 2014 ). Transcriptomics analyses showed that GT3 regulates the expression of genes related to inflammation, protein transport and cellular redox ( Tan et al, 2018 ; Tang et al, 2019 ). It has the functions of inducing cell apoptosis, inhibiting colony formation, inhibiting cell survival and cell proliferation ( Prasad et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Tan et al evidenced that platelet-derived growth factor (PDGF) signaling and cytoskeletal structure can be dysregulated in senescent HDFs. The proproliferative effect of gamma-tocotrienol on senescent HDFs may be mediated through the stimulation of cellular response to stress and carbohydrate metabolism [ 74 ].…”
Section: Is the Action Of Antioxidants Due To Their Antioxidant Acmentioning
confidence: 99%